Uterine RGS2 expression is regulated by exogenous estrogen and progesterone in ovariectomized mice, and downregulation of RGS2 expression in artificial decidualized ESCs inhibits trophoblast spreading in vitro. Issue 1 (30th November 2018) - Jiang, Manxi; Hu, Liangshan; Wang, Baoping; Chen, Danxia; Li, Yahong; Zhang, Zhen; Zhu, Yan
Abstract : Embryo implantation is a complicated event that relies on two critical factors: the competent blastocyst and the receptive uterus. Successful implantation results from tight coordination of these two factors. The maternal hormone environment of the uterus and molecular cross‐talk between the embryo and uterine tissue play pivotal roles in implantation. Here we showed that regulator of G‐protein signaling 2 (RGS2), a member of ubiquitous family of proteins that regulate G‐protein activation, plays an important role in embryo implantation by interfering in the cross‐talk between the embryo and uterine tissue. RGS2 expression increased during the implantation process, and was higher in the implant site than at the nonimplantation site. Meanwhile, ovariectomized (OVX) mice exhibited higher expression of RGS2 in the uterus. Exogenous 17β‐estradiol and progesterone in OVX mice downregulated the expression of RGS2. Treatment with exogenous 17β‐estradiol alone caused uterine RGS2 messenger RNA levels of OVX mice to return to those of normal female mice; when these mice were treated with progesterone or 17β‐estradiol plus progesterone, RGS2 levels rose. Downregulation of Rgs2 by small interfering RNA in an in vitro coculture system of decidualized endometrial stromal cells and blastocysts inhibited blastocyst outgrowth by restricting trophoblast spreading, suggesting a mechanism by which RGS2 regulates embryo implantation.